Possible Long-Term Effects of Childhood Maltreatment on Cognitive Function in Adult Women With Posttraumatic Stress Disorder - Nakayama, Michi; Hori, Hiroaki; Itoh, Mariko; Lin, Mingming; Niwa, Madoka; Ino, Keiko; Imai, Risa; Ogawa, Sei; Sekiguchi, Atsushi; Matsui, Mie; Kunugi, Hiroshi; Kim, Yoshiharu (Frontiers in Psychiatry, 2020)
Accumulated evidence shows that individuals with posttraumatic stress disorder (PTSD) have compromised cognitive function. PTSD is associated with childhood maltreatment, which also can negatively affect cognitive function. It is therefore possible that cognitive dysfunction in adult patients with PTSD can be due at least partly to childhood maltreatment, although little is documented on this issue. Here we aimed to examine the possible effect of childhood maltreatment on cognitive function in adult patients with PTSD. A total of 50 women with DSM-IV PTSD and 94 healthy control women were enrolled. Most of the patients developed PTSD after experiencing interpersonal violence during adulthood. History of childhood maltreatment was assessed using the Childhood Trauma Questionnaire (CTQ). Cognitive functions were assessed by the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS). Compared to controls, patients reported significantly more experiences of all types of childhood maltreatment as assessed by the CTQ and showed significantly poorer performance on immediate memory, language, attention, and the total score of RBANS. In patients, sexual abuse scores were significantly negatively correlated with RBANS language (p < 0.001) and total score (p = 0.005). Further analyses revealed that PTSD patients with childhood sexual abuse had even poorer cognitive function than those without the abuse. In controls, no significant correlation was found between CTQ and RBANS scores. These results suggest that childhood maltreatment, specifically sexual abuse, may lead to persistent cognitive impairment in individuals with PTSD. Our findings might underscore the importance of early detection and intervention of childhood maltreatment, which will be achieved by careful observation of, and listening to, maltreated children in education and welfare scenes as well as clinical settings.